Beastly Journeys : Travel and Transformation at the fin de siècle - Youngs, Tim, 1961- (Book collections on Project MUSE., 2013)
A critical exploration of travel, animals and shape-changing in fin de siecle literature. Bats, beetles, wolves, butterflies, bulls, panthers, apes, leopards and spiders are among the countless creatures that crowd the pages of literature of the late nineteenth century. Whether in Gothic novels, science fiction, fantasy, fairy tales, journalism, political discourse, realism or naturalism, the line between the human and the animal becomes blurred. Beastly Journeys examines these bestial transformations across a range of well-known and less familiar texts and shows how they are provoked not only by the mutations of Darwinism but by social and economic shifts that have been lost in retellings and readings of them. The physical alterations described by George Gissing, George MacDonald, Arthur Machen, Arthur Morrison, W.T. Stead, Bram Stoker, H.G. Wells, Oscar Wilde, and many of their contemporaries, are responses to changes in the social body as Britain underwent a series of social and economic crises. Metaphors of travel - social, spatial, temporal, mythical and psychological - keep these stories on the move, confusing literary genres along with the indeterminacy of physical shape that they relate. Beastly Journeys will appeal to anyone interested in the relationship between nineteenth-century literature and its contexts and especially to those interested in the fin de siecle and in metaphors of travel, animals and shape-changing.